Sosialisasi Status Tingkat Trofik Sungai Je’neberang Kabupaten Gowa Sulawesi Selatan - Meinarni Thamrin; Ulva Ria Irfan .; Meutia Farida .; Kaharuddin .; Rohaya Langkoke .; Ratna Husain .; M. Fauzi Arifin .; Haerany Sirajuddin .; Asri Jaya .; Adi Maulana .; Sahabuddin .; M. Zulhuzair B .; Baso Resky Maulana . (Faculty of Engineering UNHAS, 2022)
The Je'neberang River supports the lives of the people of Gowa and Makassar both ecologically and economically. Therefore, this river must be conserved starting from the upstream, downstream to the estuary, one of which is by assessing its trophic status. Trophic status is an indicator of the fertility level of water that can be measured from nutrients, chlorophyll-a content, brightness levels, and other biological activities that occur in an aquatic environment. This research-based community service aims to determine the trophic level status of the Je'neberang River which has been socialized to the community. Based on the output of data analysis obtained, this service activity is focused on educating partners, which is part of socialization. The method is divided into two stages, namely the stage of data collection and testing and the stage of socialization to partners. Socialization to partners is divided into four stages, namely preparation or pre-activity, preparation of socialization materials, implementation of socialization, and evaluation of the sustainability of activities. Socialization activities at the crossing location between Mallengkeri (Makassar) sub-district to the Taeng area in Gowa Regency. Socialization is in the form of countermeasures so that the rate of trophic level can be slowed down naturally, by not using the Je'neberang River as a waste disposal site. The condition of oligotrophic status on the Je'neberang River has been socialized to the community around river users, how important it is to maintain balance or nutritional conditions in the river to preserve the biota/organisms that live in the river.